Factors that influencing the household debt rise in Malaysia / Nor Arifah Abidin - Abidin, Nor Arifah (2013)
Household debt in Malaysia has continued to grow every year. This paper employs a Multiple linear regression model to explore the factors of household debt rise in Malaysia. The factor measures refer to interest rate, inflation rate, Gross Domestic Product (GDP) and the housing price. The study wants to explore how these factors can affect the household debt rise in Malaysia. The results showed that the interest rate, inflation rate and GDP and housing prices have significant relationship with the household debt. Moreover, household debt is positively related to factor measures, especially to housing price